Social Change of Downstream Triangle Community as an Impact of Kedungombo Dam Development - Surjono, Gunanto (Jurnal Penelitian Kesejahteraan Sosial, 2018)
This research is done to describe social change on the community living at downstream triangle of Kedungombo water reservoir, Central Java. Approaching model used in this research is quantitative-descriptive, which is implemented through informants choosing, gahtering and analizing data techniques as follows: Informants are choosen purposively those who saw and experieced their changing environment, form piece of farm land to water reservoir (dam). Data are gathered through interview with informants through snowball technique. The research finds that a significant change happens to the downstream triangle community during 25 years of their environmental change on the aspect of communal economy, family system, relation with local government, and local belief.